Correction: RuCo alloy trifunctional electrocatalysts with ratio-dependent activity for Zn–air batteries and self-powered water splitting. Issue 89 (28th October 2021) - Pei, Yu; He, Wangtao; Wang, Minmin; Wang, Jin; Sun, Tongming; Hu, Lanping; Zhu, Jinli; Tang, Yanfeng; Wang, Jiacheng
Abstract : Correction for 'RuCo alloy trifunctional electrocatalysts with ratio-dependent activity for Zn–air batteries and self-powered water splitting' by Yu Pei et al., Chem. Commun., 2021, 57, 1498–1501, DOI: ; 10.1039/D0CC07565E .